RUG-II Impacts on Long-Term Care Facilities in New York - Schultz, Barry M. (CENTERS for MEDICARE & MEDICAID SERVICES, 1994)
This article observes changes during the first 5 years of Resource Utilization Group, Version II (RUG-II) system utilization by the New York State Department of Health (NYDOH) for Medicaid program reimbursement. Findings include a dramatic increase in the number of residents scoring in the highest intensity resident-care categories, a substantial increase in staffing and expenditures for rehabilitation therapies, and a possible negative impact on the financial performance of New York long-term care (LTC) facilities. RUG-II appears to have been successful in improving access to nursing homes for individuals with heavy-care needs and in encouraging the appropriate utilization of institutionalized skilled nursing care.